2008
DOI: 10.1590/s0102-86502008000500005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation by computerized morphometry of histopathological alterations of the colon wall in segments with and without intestinal transit in rats

Abstract: Purpose:To evaluate histopathological alterations of the colon wall in segments with and without intestinal transit, by computer-assisted imaging, and to correlate these with the length of time diversion. Methods: Thirty male Wistar rats were subjected to intestinal transit diversion by a proximal colostomy and distal mucosa fistula. The animals were divided into three experimental groups according to how long after the initial surgical procedure they were sacrificed: six, twelve and eighteen weeks. Colon segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0
8

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 24 publications
5
41
0
8
Order By: Relevance
“…This could perhaps explain the increased expression of sialomucins during the first weeks that those authors found. This possibility is likely to be more common than is supposed 31 . In the present study, when we performed mechanical cleaning of the distal colon before the intestinal diversion, we observed that formed feces came out through the anus of all of the animals in the experimental group 37 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This could perhaps explain the increased expression of sialomucins during the first weeks that those authors found. This possibility is likely to be more common than is supposed 31 . In the present study, when we performed mechanical cleaning of the distal colon before the intestinal diversion, we observed that formed feces came out through the anus of all of the animals in the experimental group 37 .…”
Section: Discussionmentioning
confidence: 92%
“…Studies using biochemical, histochemical and immunohistochemical techniques have demonstrated that, in the different forms of colitis, abnormalities occur not only in the tissue content but also in the expression pattern of mucins along the crypts of the colon mucosa 21,22,[30][31][32][33] . These findings have made it attractive to hypothesize that the etiopathogenesis of ulcerative colitis might be related to changes in mucin production in individuals with predisposing factors, or to changes caused by intraluminal factors 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the increased OFRs production by epithelial cells with deficient SCFAs supply and the recognized deficiency of colonic mucosa in antioxidant enzymatic systems, which makes the intestinal epithelium particularly vulnerable to oxidative stress, are mechanisms related to the pathogenesis of DC 20,27 . Studies have demonstrated that oxidative stress reduces the production of mucins that cover the epithelium, promotes peroxidation of phospholipids that constitute the cytoplasmic membrane of colonocytes and breaks the intercellular connections and the basement membrane, the main components of the colonic mucosal defense systems [22][23][24][25][26] . Rupture of this defense system allows the migration of intestinal lumen bacteria into the sterile layers of colon wall.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting oxidative stress causes histological and biochemical alterations similar to those found in experimental models of chemically induced colitis or human colitis. The oxidative stress causes alterations in the colonic mucosa that aggravate according to the time of diversion [20][21][22][23][24][25][26][27] . Based on these evidences, the use of substances with antioxidant activity was suggested to be effective in the prevention and treatment of this disease 20,27 .The benefits of these substances in the treatment of DC were recently confirmed with the application of enemas with 5-aminosalicylic acid (5-ASA), a powerful antioxidant, was demonstrated to reduce the levels of tissue oxidative stress and improve the inflammatory process in the mucosa without fecal stream, even after the ex-vivo exposure to hydrogen peroxide (H 2 O 2 ) 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Histomorphometric analysis enables objective and quantifiable assessment of the organs' structure [30]. Fractal dimension is a parameter which reflects the complexity and irregularity of studied organs [31].…”
Section: Discussionmentioning
confidence: 99%